Process safety management : leveraging networks and communities of practice for continuous improvement /: leveraging networks and communities of practice for continuous improvement. ([2014]) - Lutchman, Chitram; Evans, Douglas (Douglas J.); Maharaj, Rohanie; (Safety professional), Sharma, Ramesh
No abstract available